Green Accounting: Peningkatan Environmental Performance Studi Kasus Perusahaan Semen, Energi, dan Tambang - Muhammad Fietra Winandha; Arditya Dian Andika; Enny Susilowati M; Hermawan Triono (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
Companies in the sectors of cement, energy, and mining engage in the extraction of raw materials, their subsequent processing into finished products, and the distribution or delivery of these goods. These raw materials are derived from natural resources and are essential in the production of a variety of materials. The manufacturing process produces a considerable volume of waste, which consequently affects the environment. This study aims to explore the effects of renewable energy, recycled waste, and environmental costs on environmental performance, both individually and collectively, while also evaluating these effects through experimental analysis. This study will employ a quantitative methodology, concentrating on specific sustainability reports from firms within the cement, energy, and mining sectors that are listed on the Indonesia Stock Exchange between the years 2020 and 2024. Utilizing a purposive sampling technique, this research has yielded a total of 60 data sets. The objective of this analysis is to address the research hypothesis through the application of structural equation modeling. The findings of the study demonstrate that, to a certain degree, only renewable energy possesses the capability to impact environmental performance, whereas factors such as recycled waste and environmental costs do not exert influence. It is important to acknowledge that when evaluating their cumulative effects, all methods of green accounting can alter environmental performance. Additionally, this research indicates that the evolving framework of green accounting emphasizes accounting practices associated with transactions, events, financial entities, and social and environmental processes. In light of these findings, green accounting is defined as the practice of recognizing, quantifying, documenting, reporting, and disclosing the integration of an organization’s accounting activities with its environmental performance into a unified figure, which stakeholders then utilize to inform both economic and non-economic decisions.